1991
DOI: 10.1002/jat.2550110105
|View full text |Cite
|
Sign up to set email alerts
|

Changes in urinary proximal tubule parameters in neonatal rats exposed to cadmium chloride during pregnancy

Abstract: Pregnant Sprague-Dawley rats were injected intraperitoneally with physiological saline solution (vehicle) or cadmium chloride (CdCl2) at 2.0 or 2.5 mg kg-1 on days 8, 10, 12 and 14 of gestation. On postnatal day (PND) 3, 12 or 49, the offspring were examined for 8- or 24-h urinary excretion of beta 2-microglobulin (beta 2-m), metallothionein (MT) and urinary activity of three proximal tubular enzymes: gammaglutamyl transferase (GGT), alkaline phosphatase (ALP) and N-acetyl-beta-glucosaminidase (NAG). Treatment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

1992
1992
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 20 publications
0
12
0
Order By: Relevance
“…Such alterations correlated with an increase in the levels of early kidney injury biomarkers in amniotic fluid samples that are composed of fetal urine [ 42 ]. Similarly, a previous study presented evidence that repeated doses of Cd increased β2-microglobulin excretion and lower activity of γ-glutamyl transferase, alkaline phosphatase and N-acetylglucosaminidase in the urine of 3-day old rat pups, which suggested a reduced number of nephrons or a delayed tubular maturation [ 115 ]. All these renal outcomes could be the result of Cd-induced oxidative stress caused by lower levels of glutathione (GSH), superoxide dismutase (SOD) and catalase (CAT) [ 110 ]; nevertheless, further studies are required to corroborate these conclusions.…”
Section: Effects Of CD In the Fetal Organismmentioning
confidence: 85%
See 1 more Smart Citation
“…Such alterations correlated with an increase in the levels of early kidney injury biomarkers in amniotic fluid samples that are composed of fetal urine [ 42 ]. Similarly, a previous study presented evidence that repeated doses of Cd increased β2-microglobulin excretion and lower activity of γ-glutamyl transferase, alkaline phosphatase and N-acetylglucosaminidase in the urine of 3-day old rat pups, which suggested a reduced number of nephrons or a delayed tubular maturation [ 115 ]. All these renal outcomes could be the result of Cd-induced oxidative stress caused by lower levels of glutathione (GSH), superoxide dismutase (SOD) and catalase (CAT) [ 110 ]; nevertheless, further studies are required to corroborate these conclusions.…”
Section: Effects Of CD In the Fetal Organismmentioning
confidence: 85%
“…Lastly, whether the renal effects caused by Cd gestational exposure are permanent or not, is still on debate because there is contrasting evidence that supports either possibility [ 34 , 115 ]. Discrepancies found may be the result of differences in the experimental models used, such as the period and length of exposure.…”
Section: Effects Of CD In the Fetal Organismmentioning
confidence: 99%
“…Delivery was at day O. Geometric mean _+ geometric SD of 10 rats. * p <0.05 (Kavlock et al 1986), methylmercury (Saillenfait et al 1989) or cadmium (Saillenfait et al 1991) have been shown to induce renal dysfunction in rats exposed during the prenatal period. The present study in rats demonstrates that maternal exposure to mercuric chloride can produce in mothers and their.litter a renal dysfunction resulting in an increased urinary excretion of albumin and beta2-microglobulin.…”
Section: Resultsmentioning
confidence: 95%
“…Several animal studies have evaluated the association between cadmium exposure and the risk of kidney functions during In utero or early life [128][129][130]. An In-vivo study demonstrated that accumulation of cadmium increases in the kidney from postnatal day 2 to postnatal day 60, where rats were exposed to cadmium through mother during the gestational period [130].…”
Section: Renal Dysfunctionsmentioning
confidence: 99%